PENGARUH TEKANAN KETAATAN DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT DENGAN PENGALAMAN AUDITOR SEBAGAI VARIABEL MODERATING (Students' Journal of Accounting and Banking, 2014)
This study aims to examine and analyze the effect of obedience pressure and task complexity on audit judgment with auditor experience as a consideration to determine how much influence obedience pressure and task complexity on audit judgment. The population in this study was the auditors who work on a public accounting firm in the city of Semarang. Sample selection method used was purposive sampling with a total of 52 questionnaires that can be processed. The data analysis technique used is multiple linear regression analysis. Based on the results of tests performed can be seen that obedience pressure, task complexity and experience of the auditor's positive effect on audit judgment. Moderate the influence of auditor experience stress adherence to audit judgment made​​. Auditor experience does not moderate the effect of obedience pressure on audit judgment made.Keywords: obedience pressure, task complexity, experience of auditors and audit judgment